1995
DOI: 10.1111/j.1365-2591.1995.tb00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Dens invaginatus in a mandibular lateral incisor

Abstract: A rare case of dens invaginatus involving a non-carious mandibular lateral incisor with periapical periodontitis is reported. Invaginated teeth present technical difficulties in their clinical management because of their abnormal anatomy. In the present case, non-surgical root canal therapy was chosen. A one-year follow-up clinical and radiographic examination showed a non-symptomatic tooth with osseous healing proceeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…7 Langlais et al 7 noted that the mandibular occurrence of this anomaly is rare. In fact, a review of the English language literature only showed 10 cases involving 13 mandibular teeth [9][10][11][12][13][14][15][16][17][18] and among them, involvement of mandibular incisors is limited to three cases involving four teeth. The population studies conducted in North America on the incidence of DI in large groups were limited to Caucasians, Asians and African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…7 Langlais et al 7 noted that the mandibular occurrence of this anomaly is rare. In fact, a review of the English language literature only showed 10 cases involving 13 mandibular teeth [9][10][11][12][13][14][15][16][17][18] and among them, involvement of mandibular incisors is limited to three cases involving four teeth. The population studies conducted in North America on the incidence of DI in large groups were limited to Caucasians, Asians and African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…When these minor forms of invaginations are eliminated root canal therapy in most cases will not present further problems. In certain cases the invagination has to be treated as a separate root canal (Cole et al 1978, Zillich et al 1983, Eldeeb 1984, Greenfield & Cambruzzi 1986, Mangani & Ruddle 1994, Khabbaz et al 1995.…”
Section: Root Canal Treatmentmentioning
confidence: 99%
“…However, dens invaginatus in mandibular teeth (20 -23) and specifically in mandibular lateral incisors appears to be a rare condition. Up until now, only 3 clinical cases of this anomaly have been described in the literature (21)(22)(23). The first 2 simply reported the cases, and the third described the endodontic treatment of a typical type III dens invaginatus.…”
mentioning
confidence: 97%